Pengaruh Net Profit Margin Terhadap Return On Asset Pada PT. Indofarma (Persero), Tbk - Zulwahidah, Aida; Puji Muniarty; Irma Mardian (Pusat Riset dan Inovasi Nasional, 2025)
With a focus on the years 2014–2023, this research will look at how PT. Indofarma (Persero) Tbk's Net Profit Margin (NPM) affected their Return On Assets (ROA). The company's deteriorating financial situation is the driving force for the study. This is evident in the shifting and drastically dropping data for net income, sales, and total assets, especially in 2023, which point to financial crisis. A quantitative associative research strategy is used in this investigation. The methods utilised for data analysis include t-tests, correlation coefficient tests, simple linear regression analysis, and coefficient of determination (R²), using secondary data sourced from the company's yearly financial reports. Return On Assets (ROA) is positively and significantly impacted by Net Profit Margin (NPM), according to the data. The regression coefficient is 0.007, and the significance level is 0.000 (p < 0.05). When the R² value is 1.000, it means that NPM explains all of the variance in ROA. The research found that ROA was positively correlated with NPM. To maximise asset utilisation, effective cost management and net income performance are crucial. Thus, in order to increase total profitability, PT. Indofarma needs implement methods to improve operational efficiency and financial management.